Trade, standards, and the political economy of genetically modified food - Anderson, Kym, 1950- 1950- (Policy research working paper, 2004)
"Anderson, Damania, and Jackson develop a common-agency lobbying model to help understand why North America and the European Union have adopted such different policies toward genetically modified (GM) food. Their results show that when firms (in this case farmers) lobby policymakers to influence standards, and consumers and environmentalists care about the choice of standard, it is possible that increased competition from abroad can lead to strategic incentives to raise standards, not just lower them as shown in earlier models. The authors show that differences in comparative advantage in the adoption of GM crops may be sufficient to explain the trans-Atlantic difference in GM policies. On the one hand, farmers in a country with a comparative advantage in GM technology can gain a strategic cost advantage by lobbying for lax controls on GM production and use at home and abroad. On the other hand, when faced with greater competition, the optimal response of farmers in countries with a comparative disadvantage in GM adoption may be to lobby for more-stringent GM standards. So it is rational for producers in the European Union (whose relatively small farms would enjoy less gains from the new biotechnology than broad-acre American farms) to reject GM technology if that enables them and consumer and environmental lobbyists to argue for restraints on imports from GM-adopting countries. This theoretical proposition is supported by numerical results from a global general equilibrium model of GM adoption in America with and without an EU moratorium. This paper a product of the Trade Team, Development Research Group is part of a larger effort in the group to understand the economic implications of standards and technology policies in a multilateral trading environment"--World Bank web site